THE IMPACTS OF TUTORS’ COMMUNICATION PATTERN TOWARDS IMPROVING THE TRAINEES’ LEARNING QUALITY AT THE WORK TRAINING INSTITUTE (LPK) - Rizal Mochammad Fadlyansyah; Sri Nurhayati (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2020)
The development of work training institutions in Indonesia with various skills is tremendous strength in supporting government policy to create Indonesia's high quality, intelligent, skilled, independent, and competitive human resources. The purpose of this study is (1) to describe communication patterns that are established by tutors/ instructors to improve the quality of learning at LPK Mekarsari; (2) To know the process of designing useful communication patterns in improving the learning quality of learners in LPK Mekarsari; (3) to know the impact of the effective implementation of communication patterns by tutors in LPK Mekarsari to the quality of trainees’ learning. The theory used in this research includes the concept of communication, the concept of outdoor education, work training concept, training concept, learning quality improvement concept. The study used descriptive method with simple research design approach. Data collection techniques using interviews, documentation, and observations. Based on the research carried out, the results that the tutors’ communication pattern conducted by LPK Mekarsari is assembled and has been through the process of designing a good communications pattern. Communication patterns are done directly (face-to-face) and indirectly (through communication tools), interactive and supportive, making the communication pattern organized, and trainees also actively involved. Based on the profile of graduates and achievements of trainees in LPK Mekarsari can be concluded that the communication pattern has been effective and have an impact on improving the quality of trainees’ learning in LPK Mekarsari